Мировая экономическая наука в лицах - Румянцева Елена Евгеньевна (ИНФРА-М, 2013)
Экземпляры: СЭ (20160601) / Инвентарный номер: 1098476 / Цена: / Сис.шифр: 65.02 / Авт.знак: Р 86 / ГРНТИ: 06 / ББК: 65.02(0)